2022
DOI: 10.3390/ma15124095
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Restylane Lyft Used as a Scaffold for Dental Pulp Regeneration in Non-Infected Immature Teeth in Dogs

Abstract: Commercially available hyaluronic acid dermal fillers used as a scaffold in regenerative endodontic procedures (REPs) have demonstrated attractive potentials. This study aimed to histologically evaluate the outcome of REPs using Restylane Lyft (HA) as a scaffold. REPs were performed on pulpless, immature roots in dogs (n = 69). The roots were divided into four groups: blood clot (BC), Restylane Lyft (BC + HA), negative control, and positive control. At 13 weeks postoperatively, hard tissue formation, vasculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…There was no difference regarding the type of formed tissues in both groups. (3) However; Revascularization using HA scaffolds with induced blood clot significantly enhanced tissue formation with better corono-apical extension than using HA scaffolds alone. (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference regarding the type of formed tissues in both groups. (3) However; Revascularization using HA scaffolds with induced blood clot significantly enhanced tissue formation with better corono-apical extension than using HA scaffolds alone. (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown promising results when FDA-approved Restylane Lyft sterile injectable dermal filler was used as a scaffold for pulp regeneration in vitro and in immature teeth in vivo. (2,3) However, to date, the performance of Restylane Lyft hasn't been histologically investigated as scaffold in mature teeth.…”
Section: Introductionmentioning
confidence: 99%
“…These biomaterials are expanded in vitro to environmentally mimic the in vivo condition. (71,72) Ideal scaffolds for regenerative endodontic therapy should resemble the extracellular matrix (ECM) of pulp-dentin complex in terms of dimensional stability, sufficient porosity with adequate particle size, similar biodegradability rate, as well as physical and mechanical strength (71,73,74), since biocompatibility is highly important to prevent adverse tissue reactions. (75) Bioscaffold for regenerative endodontic therapy includes broad ranges of applications and sources.…”
Section: Regenerative Endodonticsmentioning
confidence: 99%
“…(96) For the regeneration of pulp and dentin-like tissue, polymers like collagen, gelatin, fibrin, chitosan, and HA have shown the ability to improve root development, including increase root length, root thickness, and enhance the mineralization of root canal. (73,89,91,93,94,(96)(97)(98) While being used as a single scaffold, those natural polymers also showed better ability in increasing intracanal connective tissue formations and narrowing apical width compared with BC, healing the periapical lesion, increasing dental wall thickness, as well as resuming the maturation process for the immature teeth. (73,(88)(89)(90)93,98) Natural polymers are often combined and crosslinked with other bioscaffold or chemical agents to improve its potential in regenerative therapy.…”
Section: Blood-derivedmentioning
confidence: 99%
See 1 more Smart Citation